Memristive Devices: Planar and Transparent Memristive Devices Based on Titanium Oxide Coated Silver Nanowire Networks with Tunable Switching Voltage (Small 21/2021). Issue 21 (27th May 2021) - Resende, Joao; Sekkat, Abderrahime; Nguyen, Viet Huong; Chatin, Tomy; Jiménez, Carmen; Burriel, Mónica; Bellet, Daniel; Muñoz‐Rojas, David
Abstract : In article number 2007344, Daniel Bellet, David Muñoz‐Rojas, and co‐workers demonstrate transparent resistive switching devices entirely fabricated by open‐air approaches, without a deposition chamber. The threshold voltage can be tuned by adjusting the density of AgNWs, while maintaining a high LRS/HRS ratio. The researchers show the effect of oxide thickness on the threshold‐switching phenomenon, thus shedding light on the conduction mechanism of this type of switching devices.